2017
DOI: 10.1111/rec.12493
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the post‐recolonization of Antechinus flavipes and its genetic implications in a production forest landscape

Abstract: Production landscapes, where activities such as timber harvesting, grazing, and resource extraction take place, have considerably reduced the extent of natural habitats. The ecological restoration of these landscapes is, in many cases, the best remaining option to protect biodiversity. However, it is unclear whether restoration designed to avert biodiversity loss in restored landscapes can also maintain genetic diversity in recolonizing faunal populations. We employed core concepts in the field of population g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…To better integrate connectivity into restoration practice, it is also important to explicitly evaluate the impacts of restoration projects on genetic connectivity, not only during translocations (Aavik et al ; Reynolds et al ), but also in species that naturally recolonize restored habitat (Cosentino et al ; Isselin‐Nondedeu et al ; Mijangos et al ). When evaluating the restoration of habitat for connectivity, it is important to note that “gene flow” should be considered as the incorporation via reproduction of genes into another population; “movement” of genes alone is insufficient to realize the fitness benefits of gene flow.…”
Section: Translation Into Practicementioning
confidence: 99%
See 2 more Smart Citations
“…To better integrate connectivity into restoration practice, it is also important to explicitly evaluate the impacts of restoration projects on genetic connectivity, not only during translocations (Aavik et al ; Reynolds et al ), but also in species that naturally recolonize restored habitat (Cosentino et al ; Isselin‐Nondedeu et al ; Mijangos et al ). When evaluating the restoration of habitat for connectivity, it is important to note that “gene flow” should be considered as the incorporation via reproduction of genes into another population; “movement” of genes alone is insufficient to realize the fitness benefits of gene flow.…”
Section: Translation Into Practicementioning
confidence: 99%
“…Differences in mutation rates and inheritance patterns of genetic markers can be exploited to estimate and contrast patterns of historical and contemporary genetic connectivity. For example, Mijangos et al () used a mitochondrial DNA marker and microsatellites to reconstruct regional historical migration rates and population sizes of a small marsupial across a landscape containing restored mine sites. They then used microsatellite markers to assess whether postmining rehabilitation restored contemporary connectivity to recolonizing populations at a local scale.…”
Section: Establishing Historical Baselinesmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as land clearing, threats such as introduced predators (feral cats, Felis catus and foxes, Vulpes vulpes) and climate change may have caused population reductions in A. mysticus and will likely continue to negatively affect both species and many other mammals (Woinarski et al, 2015). Indeed, a recent microsatellite study identified that land clearing and related anthropogenic changes are driving a substantial decline in the population size of southwestern Australian A. flavipes (Mijangos, Pacioni, Spencer, Hillyer, & Craig, 2017). However, the evidence of decline throughout the range of A. mysticus, which is possibly severe at Cooloola, suggests that A. mysticus is at a more immediate extinction risk than A. subtropicus.…”
Section: Conservationmentioning
confidence: 99%